Lithium storage performance and mechanism of nano-sized Ti2InC MAX phase. Issue 3 (9th January 2023) - Xu, Xueqin; Sha, Dawei; Tian, Zhihua; Wu, Fushuo; Zheng, Wei; Yang, Li; Xie, Shengyu; Zhang, Peigen; Sun, ZhengMing
Abstract : Nano-sized Ti2 InC prepared by ball milling combines the benefits of insertion-type and alloy-type electrodes and thus has a favorable capacity and long cycling life, suggesting that downsized MAX phases would be a promising anode. Abstract : Fine powders of MAX phases (a family of layered carbides/nitrides) have been showing great promise in energy storage applications. A feasible method of obtaining nano-sized MAX phase particles is critical to realizing the practical application of the vast MAX phase family in more technologically important fields. Herein, ball milling, a commercial and feasible method, is employed to prepare nano-sized Ti2 InC, which delivers a high specific capacity of 590 mA h g −1 after 500 cycles and maintains 574.4 mA h g −1 after 600 cycles at 0.1 A g −1 when used as a lithium storage anode. Compared with other methods ( e.g., partial etching), decreasing the size of Ti2 InC particles by ball milling can preserve the exfoliated indium (In) atoms, which have great volumetric and gravimetric capacities. In situ XRD analysis indicates that the capacity of the nano-sized Ti2 InC primarily comes from the lithiation of elemental In exfoliated from Ti2 InC, and in particular, the exfoliated In atoms by ball milling can increase the initial capacity. The lithiation/delithiation cycle can effectively activate and even exfoliate the Ti2 InC grains, which accounts for the increasing capacity upon cycling.